Pengaruh Pengetahuan Pajak dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi Bangunan (Studi kasus pada Kelurahan Nangalimang Kecamatan Alok Kabupaten Sikka) - Marialen Rosfinte Nona Lado (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to determine the effect of tax knowledge and taxpayer awareness on taxpayer compliance in paying Land and Building Tax (PBB) in Nangalimang Village, Alok District, Sikka Regency. The research method used is a quantitative method and a survey approach. The data used in this study are primary data in the form of questionnaires distributed to taxpayers 2who are registered in the Nangalimanang Village, Alok District, Sikka Regency. The sampling technique used the slovin formula, with a total of 90 respondents distributed questionnaires. The results of this study indicate that the results of the F test have a significance value of 0.000 which is less than the alpha level used, which is 0.05 or 5%. The results of the T test show that a) the significance value of tax knowledge is 1,995 > 1,987; b) the significance value of taxpayer awareness is 4,860 > 1,987. it can be seen that simultaneously there is influence from tax knowledge and awareness of taxpayers on taxpayer compliance with land and building taxes.